KAJIAN SISTEM POLINASI DAEMONOROPS DRACO (WILLD.) BLUME - Revis Asra; Syamsuardi Syamsuardi; Mansyurdin Mansyurdin; Joko Ridho Witono (Floribunda, 2013)
The pollination study on Daemonorops draco (Wildd.) Blume has been conducted based on structure of inflorescence, pollen and ovul ration, and apomixis. The result of study present that inflorescence structure of D. draco was androdioecious. Based on the color of the inflorescence on anther and crown indicated that D. draco pollination systems supported by insects (Trigona spp.). Pollination systems of D. draco based on ratio pollen ovule is xenogami (outcrossing). Apomixis process proved that fruit of D. draco can be formed without convergence of gametes/males and females which have the character of apomixis.